(untitled) (Islamic Sciences Journal, 2023)
The science of faith is a great science, and high, because all judgments and branches depend on it, it is the cornerstone of the building, and health require the health of the building, has been sent God the apostles (peace be upon them) to consolidate the belief in the hearts of people teach them password unification which mushroom God’s people them, the more related to the heart of the servant standardization of God has increased to know him names and attributes. This is a research that ensures the status of the renewed world, the Amir of the Believers Omar bin Abdul Aziz (may God have mercy on him), And the extent of his defense of the resemblance to the nodal, which was raised and developed in the past time, and Omar bin Abdul Aziz (may Allah have mercy on him) has followed the approach in the doctrine of doctrine of good argument And the constructive debate in the consolidation and consolidation of science, and was (God’s mercy) away from the use of force and coercion in persuading the difference and its founders, and was (God’s mercy) a lot of inference the texts of the Koran and Sunnah in his debates.